KOLABORATIF GOVERNANCE DALAM PENANGGULANGAN COVID-19 DI WILAYAH KABUPATEN LINGGA - ZAMRONI, ZAMRONI (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The government has continued to undertake intensive measures to combat COVID-19 since the beginning of March 2020 to lower the pace of COVID-19 spread. Based on preliminary findings, there is a collaborative approach in Lingga Regency that has not been fully utilized, with indications of a lack of material assistance in addressing the needs of facilities and infrastructure from every village in the regency. The goal of this study is to look into